FORMULATION A CIPROFLOXACIN HYDROCHLORIDE EXTENDED-RELEASE TABLET WITH COMBINATION OF HYDROXYPROPYL METHYLCELLULOSE (HPMC) K100M AND HYDROXYPROPYL METHYLCELLULOSE (HPMC) K4M BY DIRECT COMPRESSION METHOD - MUSTARICHIE, RESMI; GOZALI, DOLIH; HERDIANA, YEDI (International Journal of Applied Pharmaceutics, 2020)
Objective: Ciprofloxacin hydrochloride tablets which are not extended-release will produce non-constant drug levels in the blood. This study aimed to overcome this problem by making ciprofloxacin hydrochloride extended-release tablets with a combination of hydroxypropyl methylcellulose (HPMC) K100M and hydroxypropyl methylcellulose (HPMC) K4M by a direct compression method. Methods: The method in this study consisted of preformulation, formula design, manufacture of ciprofloxacin hydrochloride tablets, tablet print mass testing, IPC (In-Process Control) slow-release tablet mass print, IPC (In-Process Control) quality of slow-release tablet preparation, dissolution test, and statistical analysis. Preformulation was carried out aiming to determine the physical and chemical properties of active-excipient substances based on a certificate of analysis. This was done using a Fourier Transform Infrared (FT-IR) and UV-Vis spectrophotometer. Five kinds of ciprofloxacin hydrochloride tablet formulations were made using the direct pressing method with variations in the concentration of HPMC K100M and HPMC K4M. The ratio of percentage of HPMC K100M and HPMC K4M were F1 0,5%: 1%, F2 1%: 0,5%, F3 0,75%: 0,75%, F4 1%: 0%, F5 0%: 3%. Evaluation of tablet preparations (IPC control) included weight uniformity test, size uniformity test, hardness test, and friability test. The dissolution test was carried out for 2 h by hydrochloride acid 0,1 N pH 1.2 as (pH of gastric acid). Statistical analysis using Perfect Block Random Design (PBRD) method and further testing using the Newman-Keuls test was applied for the data obtained. Results: The test results with FTIR showed that ciprofloxacin hydrochloride used compared to ciprofloxacin hydrochloride BPFI is equivalent and has a purity index of 0.992739. Determination of the level of the active ingredient ciprofloxacin hydrochloride was carried out by measuring the absorbance of a 5 ppm sample solution at a wavelength of 276 nm. The percentage of absorbance of the solution is then calculated and the result obtained is 98.87%. The range of levels that have been set is 98%-102%. These test results were under those listed on the certificate of analysis. The results of the IPC test in the form of weight uniformity test, size uniformity test, hardness test, friability test, and uniformity of ciprofloxacin hydrochloride levels in the preparation, showed all data obtained fulfilling the requirements set by USP 36 convention (2013). The result from dissolution tablet test on 30, 60, and 120 min showed the release of active substance on F1 56.00 %, 67.76 %, and 87.57 %. F2 were 53.42 %, 65.16 %, and 91.44 %. F3 were 59.18 %, 72.15 %, and 91.20 %. F4 were 50.51 %, 70.70 %, and 95.29 %. F5 were 53.75 %, 69.55 %, and 92.05 %. Statistical analysis was applied for the data obtained. Dissolution results illustrated the level of active substances dissolved in the dissolution medium for 2 h or in other words the dissolution test results indicated the number of active substances from tablets that were released and enter the digestive tract and came in contact with body fluids. Conclusion: The dissolution test results as a basis of extended-release tablets showed all of the formulae met dissolution requirements of the United States Pharmacopeia (USP) 36 convention.